2014
DOI: 10.1038/bjc.2014.372
|View full text |Cite
|
Sign up to set email alerts
|

The roles of HOXD10 in the development and progression of head and neck squamous cell carcinoma (HNSCC)

Abstract: Background:HOX gene expression is altered in many cancers; previous microarray revealed changes in HOX gene expression in head and neck squamous cell carcinoma (HNSCC), particularly HOXD10.Methods:HOXD10 expression was assessed by qPCR and immunoblotting in vitro and by immunohistochemistry (IHC) in tissues. Low-expressing cells were stably transfected with HOXD10 and the phenotype assessed with MTS, migration and adhesion assays and compared with the effects of siRNA knockdown in high-HOXD10-expressing cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 41 publications
3
43
0
5
Order By: Relevance
“…Epidemiological and laboratory studies have shown that HPV infections, particularly HPV 16 and HPV 18, serve as main instigators for the development of HNSCC. Other risk factors for HNSCC include epigenetic regulation of gene expression, which may lead to the induction and progression of HNSCC (Bragado et al, 2012;Hakami et al, 2014). Increasing evidence suggests that promoter methylation of tumor-related genes can aggravate the disease in HNSCC (Laytragoon-Lewin et al, 2013;Rettori et al, 2013;Warta et al, 2014;Shi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and laboratory studies have shown that HPV infections, particularly HPV 16 and HPV 18, serve as main instigators for the development of HNSCC. Other risk factors for HNSCC include epigenetic regulation of gene expression, which may lead to the induction and progression of HNSCC (Bragado et al, 2012;Hakami et al, 2014). Increasing evidence suggests that promoter methylation of tumor-related genes can aggravate the disease in HNSCC (Laytragoon-Lewin et al, 2013;Rettori et al, 2013;Warta et al, 2014;Shi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…HOXD10 is overexpressed in some HNSCC cells, and some cell lines derived from OPMLs. This pattern was also seen in tissues, and HOXD10 expression is reduced in cells from lymph node metastases, compared with their paired primary tumours . When HOXD10 expression was increased in low‐expressing OPL and metastatic cells, there was a resultant increase in proliferation, migration and adhesion, but a decrease in invasion.…”
Section: Hoxd Clustermentioning
confidence: 74%
“…Two novel targets of HOXD10 were also identified. miR‐146a is an inhibiter of proliferation and is downregulated by HOXD10 , whilst AMOT‐p80 expression is promoted by HOXD10 and is associated with increased proliferation .…”
Section: Hoxd Clustermentioning
confidence: 99%
“…HOXD10, by contrast, has been found to exert anti-angiogenic activity, and inhibited migration and sprouting when overexpressed in venous endothelial cells (Myers et al, 2002). In addition, both negative and positive roles for HOXD10 in (tumor) cell proliferation, migration, and invasiveness have been reported, depending on the specific cell line analyzed (Cho et al, 2008;Hakami et al, 2014;Sharpe et al, 2014;Yang et al, 2015;Zha et al, 2012). Taken together, this indicates that HOXD10 exerts different functional roles in different cell types.…”
Section: Discussionmentioning
confidence: 99%